Static and dynamic modeling of a 3-axis thermal accelerometer - Silva, C. S. (2012)
A novel 3 dimensional model using a coupled fluidic-solid-interaction (FSI) approach is used to simulate the response of a 3-axis thermal accelerometer. The model is fully parametric, enables static and dynamic analysis and includes thermal dependent properties on both solid and fluidic domains. Unlike previous modeling approaches found in literature, the proposed model can be used to determine the power required for sensor operation, bandwidth and quality factor, and, due to the three dimensional approach, it is possible to use the total temperature variation along the temperature sensors (previous 2D models only give temperature differences in a single point) to simulate a more real sensor response. The model was applied to a polymer based 3-axis thermal accelerometer and simulation results using the proposed model show a power consumption of 23 mW and a sensitivity of 1 mV/g and 368 μV/g in the XY and Z directions respectively.